Are the relatives satisfied with the nurses' attitude towards patients at the filter clinic (uth) lusaka - Maseka, Mildred (Lusaka: University of Zambia , School of Medicine, 1988)
The study was conducted at the university teaching hospital at filter clinic. The aim of the study was to find out whether relatives are satisfied with the nurses' attitude towards their patients at the filter clinic. The sample size consisted of 49 patients' relatives who were at the filter clinic with their relatives.
A study submitted in partial fullfilment of the requirements for the award of a Diploma in Nursing.
Includes bibliographical references.
Keywords: Patient Satisfaction; Nurse-Patient Relations